Nitrosopumilus as main source of isoprenoid glycerol dialkyl glycerol tetraether lipids in the central Baltic Sea - Wittenborn, Anna Katharina; Bauersachs, Thorsten; Hassenrück, Christiane; Käding, Katja; Wäge-Recchioni, Janine; Jürgens, Klaus; Arz, Helge Wolfgang; Kaiser, Jérôme (Frontiers in Microbiology, 2023)
Nitrososphaeria in the phylum Crenarchaeota, is a widespread archaeal class in the oceanic realm, playing an important role in the marine carbon and nitrogen cycle. Nitrososphaeria-derived membrane lipids, i.e. isoprenoid glycerol dialkyl glycerol tetraethers (GDGTs), are commonly employed to reconstruct past water temperatures using the TetraEther indeX of 86 carbon atoms (TEX86). This index is of particular importance for the brackish Baltic Sea as to date it appears to be the only applicable organic temperature proxy. In this study, we investigated the distribution of intact and core GDGTs and their potential source organisms in the water column of three deep basins located in the central Baltic Sea to evaluate the application of TEX86. A lipidomic approach on suspended particulate matter was combined with the molecular techniques 16S rRNA gene amplicon sequencing and CARD-FISH. The archaeal community was dominated by Nitrosopumilus (~83-100% of the total archaeal sequences). As other detected taxa known to produce GDGTs each represented less than 2% of the total archaeal sequences, Nitrosopumilus is likely the most dominant GDGT producer in the central Baltic Sea. However, the occurrence of phosphohexose (PH), instead of hexose-phosphohexose (HPH) headgroups, suggested that Nitrosopumilus in the Baltic Sea may differ physiologically from representatives of marine settings and other marginal seas, such as the Black Sea. In the Baltic Sea, Nitrosopumilus is most abundant in the suboxic zone, where intact cells peak according to both CARD-FISH data and intact polar lipid concentrations. The presented data therefore suggest that TEX86 reflects subsurface rather than surface temperature in the central Baltic Sea.